Pengaruh Kualitas Pelayanan dan Promosi terhadap Minat Beli Konsumen : Survei pada konsumen di Mini Market Cicadas Kota Tasikmalaya - Edwin Bahrudin; Rita Tri Yusnita; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect simultaneously and partially of Quality of service, Promotion, Consumer Purchase Interest in Cicadas Mini market Tasikmalaya City. The method used in this research is method a survey. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the Quality of service, Promotion simultaneously have a significant effect on Consumer Purchase Interest. Quality of service partially significant effect on Consumer Purchase Interest. promotion has a significant effect on Consumer Purchase Interest.